PERAN SOFT SKILL DALAM MEMPERSIAPKAN FRESH GRADUATE MEMASUKI DUNIA KERJA: ANALISIS MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI PERGURUAN TINGGI KABUPATEN GARUT - Lathif, Muhammad Abdul; Kurniawan, Deri Alan; Adiatama, Dani (LPPM STIE Muhammadiah Bandung, 2025)
This research was conducted to determine the effect of Soft Skills on job readiness, mediated by work motivation, for Fresh Graduates at universities in Garut Regency. The research metho uses a quantitative descriptive approach, where the population includes all Fresh Graduates from universities in Garut Regency, and a sample of 100 people was taken. The sample was selected using a non-probability sampling technique, with the criteria that respondents were male and female Fresh Graduates who graduated in one period in 2024 from universities with